Antibody response to vaccination after haematopoietic cell transplantation in children using a reduced dose schedule—A retrospective cohort study. (16th October 2019) - Jensen, Lotte; Poulsen, Anja; Nygaard, Ulrikka; Scheike, Thomas; Riis, Margit Schilling; Pedersen, Freddy Karup; Heilmann, Carsten
Abstract: Children receiving HCT loose protective immunity to vaccines received pre‐HCT. Therefore, revaccination post‐HCT is of major importance. In Denmark, a vaccination schedule with fewer doses post‐HCT has been used, including two doses for diphtheria, tetanus, polio, measles, mumps, and rubella, and one dose only for Haemophilus influenzae type B. The background for this was the presumption that post‐HCT immunization constituted booster vaccination of donor immunity. Our objective was to evaluate the proportion of children protected after the scheduled vaccination programme. A nationwide retrospective cohort study of all children who have received an HCT in Denmark during 1994‐2012. Antibody levels were analysed in blood samples drawn before and after vaccination, and the probability of achieving protection after the scheduled immunization programme was estimated. A total of 198 children were included. The protection post‐immunization was as follows: diphtheria 75.3%, tetanus 89.1%, polio 97.7%, and Haemophilus influenzae type B 94.8%. For diphtheria and tetanus, the probability of achieving protection increased to 93.8% and 97.3%, respectively, after a third dose. For measles, mumps, and rubella, the probability of achieving protection was 89.4%, 80.9%, and 94.2%, respectively. In conclusion, our findings support a more extensive vaccination schedule including three doses for diphtheria and tetanus which are in line with current international guidelines.